Refuges and host shift pathways of host-specialized aphids Aphis gossypii - Xiang-Dong Liu (Nature Portfolio, 2017)
Abstract Polyphagous cotton-melon aphid populations usually comprise cotton- and cucurbit-specialized biotypes. Host-specialized aphids are prone to food shortages. Cucumber, the favourite food of cucurbit-specialized aphids, is usually absent during autumn and winter in Nanjing, China. Therefore, suboptimal host plants act as refuges and govern the population dynamics of this aphid. The species, growth stages and leaf ages of host plants that cotton- and cucurbit-specialized aphids potentially could use were explored in this study. Cotton-specialized aphids were found to use wild chrysanthemum, potato, zucchini, pumpkin and flowering cucumber besides cotton, whilst cucurbit-specialized aphids were able to utilize potato, zucchini, pumpkin and mature cotton besides cucumber. The population dynamics and genotype frequencies of aphids on hibiscus, cotton, zucchini, cucumber and pumpkin showed that cotton-melon aphids on cucumber could transfer onto mature cotton. Aphids on zucchini shared microsatellite genotypes with aphids on cotton and cucumber. The predominant genotype of aphids on cotton was found on hibiscus, but the predominant genotype on cucumber was not found on hibiscus. Host-specialized aphids clearly have refuges during food shortages. Hibiscus is an overwintering host for cotton-specialized aphids but not for cucurbit-aphids. Removing refuges or managing aphids on refuges could potentially be an effective method to control cotton-melon aphids.